Persepsi Millenials terhadap Penggunaan Media Sosial Youtube Sebagai Media Content Video Creative: Studi Deskriptif pada Pengguna Youtube di Kecamatan Tapian Dolok Kabupaten Simalungun - Prayogi, Yovaldi; Husni Ritonga, Muhammad (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
The world of creativity in Indonesia is increasingly developing. One of them is the development of creativity in YouTube content. YouTube as a new form of mass media in the development of increasingly sophisticated technology has a variety of viewers who fulfill their daily needs for information. This YouTube phenomenon has also given rise to new jobs such as those usually called YouTube users. The large number of YouTube users as a medium for creative video content gives rise to various perceptions for those who access it. This research aims to describe the perceptions of millennial generation YouTube users in Tapian Dolok District. By using qualitative research with a descriptive type. Based on the research results presented by researchers in the previous discussion, it can be concluded that there are two millennial perceptions of YouTube as a creative video content medium.